2005
DOI: 10.1016/j.scitotenv.2004.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Metal contamination of soils and crops affected by the Chenzhou lead/zinc mine spill (Hunan, China)

Abstract: In 1985, the collapse of the tailing dam in Chenzhou lead/zinc mine (Hunan, southern China) led to the spread of mining waste spills on the farmland along the Dong River. After the accident, an urgent soil cleaning up was carried out in some places. Seventeen years later, cereal (rice, maize, and sorghum), pulses (soybean, Adzuki bean, mung bean and peanut), vegetables (ipomoea, capsicum, taro and string bean) and the rooted soils were sampled at four sites: (1) the mining area (SZY), (2) the area still covere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
270
7
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 590 publications
(322 citation statements)
references
References 18 publications
36
270
7
9
Order By: Relevance
“…This study showed that cultivated crops were also significantly contaminated by Pb, particularly near the mine site. These results are inconsistent with those observed by Liu et al (2005). According to the criteria set by Baker and Brooks (1989), there were 3 plant species, including R. communis, T. candida and D. orientalis, to be considered as Pb hyper accumulators in the study area.…”
Section: Cu and Zn Concentrations In Soilscontrasting
confidence: 78%
“…This study showed that cultivated crops were also significantly contaminated by Pb, particularly near the mine site. These results are inconsistent with those observed by Liu et al (2005). According to the criteria set by Baker and Brooks (1989), there were 3 plant species, including R. communis, T. candida and D. orientalis, to be considered as Pb hyper accumulators in the study area.…”
Section: Cu and Zn Concentrations In Soilscontrasting
confidence: 78%
“…Substantial increase in cell wall thickness in root epidermis, presumably, was involved in declining level of As concentration in roots and concomitant reduction of As level in the shoots of SNP + As-treated plants. Epidermal thickness is one of the mechanisms that plant can develop to limit metal absorption in roots (Liu et al 2005;Probst et al 2009). The lowering of As-induced toxicity due to priming of exogenous NO was also supported by the normal level of leaf chlorophyll and carotenoids and reduced level of RO, an indicator of higher ROS generation, in the roots of Astreated P. vulgaris seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, growing rice aerobically results in a marked decline in As accumulation in the rice Li et al, 2009b;Hua et al, 2011;Somenahally et al, 2011;Spanu et al, 2012). However, Cd and As often occur together as contaminants in agricultural soils (Liu et al, 2005) and it is therefore necessary to investigate the feasibility of simultaneously mitigating both As and Cd accumulation in rice grains through appropriate water management.…”
Section: Introductionmentioning
confidence: 99%